Decision Support System for Tuition Fee Deduction using Simple Additive Weighting - sagala, Novi Ms. (Jurusan Teknologi Informasi Universitas Semarang, 2020)
One of tools to get attention from student candidates was offered by UKRIDA was scholarship. Scholarship offered by UKRIDA for student candidates were tuition fee deduction and were implemented selectively according to the rules. The decision support system was built using SAW method as a simple and efficient method. The tuition fee deductions comprised of three types namely: National Exam score, school report card score and courses score (mathematics and English only). The weights for each criteria and sub-criteria was determined by applied provision in university. The result of the system was the number of deduction for each student candidate based on the major.